Emerging Therapies in the Treatment of Early Childhood Wheeze - Abrams, Elissa M. (Pediatr Allergy Immunol Pulmonol, 2019)
Phenotypic variation in asthma, especially early childhood asthma, is increasingly recognized. Although inhaled corticosteroids are recommended as first-line therapy, it has less efficacy in controlling intermittent wheeze due to viral-induced symptoms in early childhood. This article reviews 2 emerging therapies in particular for early childhood wheeze: azithromycin and bacterial lysate therapy. Azithromycin's effects are both antibacterial and anti-inflammatory, and it has been shown in 2 studies in preschoolers to prevent progression to severe respiratory tract infection and decrease duration of wheeze. Bacterial lysates work at multiple stages in the innate and adaptive immune response and have been shown to decrease mean wheeze duration in particular in the preschool age. More research is required although both therapies offer a promising future approach, in particular in the nonatopic preschool wheezer, as we move toward a more personalized approach to childhood asthma.